Blockade of T‐cell receptor with Ig and ITIM domains elicits potent antitumor immunity in naturally occurring HBV‐related HCC in mice. Issue 3 (17th March 2023) - Wu, Yuwei; Hao, Xiaolei; Wei, Haiming; Sun, Rui; Chen, Yongyan; Tian, Zhigang
Abstract : Background and Aims: Chronic HBV infection is the leading cause of HCC and a serious health problem in China, East Asia, and North African countries. Effective treatment of HBV‐related HCC is currently unavailable. This study evaluated the therapeutic potential of T‐cell immunoreceptor with Ig and ITIM domains (TIGIT) blockade in HBV‐related HCC. Approach and Results: A mouse model of spontaneous HBV‐related HCC was generated by replacing wild‐type hepatocytes with HBsAg + hepatocytes (namely HBs‐HepR mice). The tumors in HBs‐HepR mice were inflammation‐associated HCC, similar to HBV‐related HCC in patients, which was distinguished from other HCC mouse models, such as diethylnitrosamine‐induced HCC, TGF‐β‐activated kinase 1 knockout–induced HCC, HCC in a stelic animal model, or NASH‐induced HCC. HCC in HBs‐HepR mice was characterized by an increased number of CD8 + T cells, whereas the production of IL‐2, TNF‐α, and interferon‐gamma (IFN‐γ) by intrahepatic CD8 + T cells was decreased. Increased expression of TIGIT on CD8 + T cells was responsible for functional exhaustion. The therapeutic effect of TIGIT blockade was investigated at the early and middle stages of HCC progression in HBs‐HepR mice. TIGIT blockade reinvigorated intrahepatic CD8 + T cells with increased TNF‐α and IFN‐γ production and an increased number of CD8 + T cells in tumors, thereby slowing the development of HCC in HBs‐HepR mice. Blocking PD‐L1 did not show direct therapeutic effects or synergize with TIGIT blockade. Conclusions: Blockade of TIGIT alone enhanced the antitumor activity of CD8 + T cells during the progression of HBV‐related HCC in a spontaneous HCC mouse model. Abstract :